(untitled) (American Journal of Islam and Society, 2015)
With so much focus on illiteracy, we sometimes forget the dire state of affairs in our urban centers with regard to education. Education in the Muslim world has increasingly regressed into an exercise of rote learning, a mass of discrete knowledge, and a frenzied race toward what we deem “useful” skills. By showing the ground reality in private education in Karachi, Pakistan, this article strives to highlight the cyclical and future-oriented trends in schools that are inimical to the very spirit of education. In doing so, it emphasizes the need to adopt thinking as the primary skill taught to students in schools, with everything else encompassed within its fold. While Karachi is a case study here, the importance of creating thinking cultures within schools is a crucial and very relevant concept to schools everywhere in the world, including the United States.